Paternal Imprisonment and Father–Child Relationships: A Systematic Review - Venema, Simon D. (Criminal justice and behavior, 2022)
Although father–child relationships (FCRs) are central to children’s experience of paternal imprisonment, few studies address this subject. A systematic review was conducted to synthesize the literature on paternal imprisonment and FCRs. Four academic databases were searched for peer-reviewed studies. Thirty studies were identified. It was found that FCRs most often deteriorate due to paternal imprisonment, but sometimes remain stable or change positively. Four key factors were found to influence FCRs: (a) the quality of preprison FCRs, (b) the frequency and experience of father–child contact during imprisonment, (c) the child’s primary caregivers’ role in facilitating father–child contact, and (d) prison barriers for maintaining FCRs during imprisonment. The interplay between these factors is essential for understanding FCRs in this context, which may explain children’s divergent experiences of paternal imprisonment. An integrated framework of FCRs in the context of paternal imprisonment is presented. Limitations and directions for research are discussed.